First report of pistachio dieback and canker caused by Fusarium proliferatum in Turkey - Oren, Emel; Palacioglu, Gulsum; Bayraktar, Harun (Springer, 2023)
[Abstract Not Available]
Keywords: Dieback and canker Pistachio Fusarium proliferatum